2016
DOI: 10.1189/jlb.1a0815-342r
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-IIA regulates leukemia engraftment and brain infiltration in a mouse model of acute lymphoblastic leukemia

Abstract: Leukemia dissemination (the spread of leukemia cells from the bone marrow) and relapse are associated with poor prognosis. Often, relapse occurs in peripheral organs, such as the CNS, which acts as a sanctuary site for leukemia cells to escape anti-cancer treatments. Similar to normal leukocyte migration, leukemia dissemination entails migration of cells from the blood circulation into tissues by extravasation. To extravasate, leukemia cells cross through vascular endothelial walls via a process called transen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 52 publications
(74 reference statements)
0
27
0
Order By: Relevance
“…Future work is expected to shed light on the mechanistic roles for IL‐15‐mediated signaling in brain metastasis. In addition to the potential for an IL‐15/IL‐15R auto/paracrine axis, feedback loops may result in upregulation of cytokine and chemokine receptors that mediate lymphoblastic infiltration into meningeal spaces and/or intracellular players that govern transmigration, such as myosin‐IIA . The NALM6 model may be particularly useful for understanding processes that lead to leukemia invasion of brain parenchyma, which was associated with only 10% of cases in a 1972 study of 126 autopsies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work is expected to shed light on the mechanistic roles for IL‐15‐mediated signaling in brain metastasis. In addition to the potential for an IL‐15/IL‐15R auto/paracrine axis, feedback loops may result in upregulation of cytokine and chemokine receptors that mediate lymphoblastic infiltration into meningeal spaces and/or intracellular players that govern transmigration, such as myosin‐IIA . The NALM6 model may be particularly useful for understanding processes that lead to leukemia invasion of brain parenchyma, which was associated with only 10% of cases in a 1972 study of 126 autopsies .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential for an IL-15/IL-15R auto/paracrine axis, feedback loops may result in upregulation of cytokine and chemokine receptors that mediate lymphoblastic infiltration into meningeal spaces [25][26][27] and/or intracellular players that govern transmigration, such as myosin-IIA. 62 The NALM6 model may be particularly useful for understanding processes that lead to leukemia invasion of brain parenchyma, which was associated with only 10% of cases in a 1972 study of 126 autopsies. 35 Case reports of intracerebral metastases remain relatively rare 32,37,38 ; because these cases were all associated with relapse, it is possible that occasional intraparenchymal colonies can offer leukemia cells sanctuary from standard treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Phase contrast and fluorescent images were acquired every 15–25 s using a 20X Phase-2 objective for 30 min long time-lapses using a Spinning Disk confocal microscope with environmental control (Intelligent Imaging Innovations) and Slidebook imaging software (Intelligent Imaging Innovations). Using similar criteria as previously described ( 11 , 29 ), a cell was scored as having undergone transendothelial when it lost its white phase ring in a step-wise process during the course of the time-lapse.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, data have shown that genes involved in cytoskeletal remodeling and cell migration play an important role in lymphoma progression in vivo ( 10 ). We recently reported that the cytoskeletal motor protein Myosin-IIA is required for leukemia migration, progression and entry into the Central Nervous System ( 11 ). However, the role of specific cytoskeletal effector proteins in leukemia migration and progression in vivo is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic analysis has suggested that in breast cancer cells, MHC (myosin heavy chain) phosphorylation sites were activated during integrin engagement and lamellar extension on fibronectin [30]. Although myosin II is not indispensable for the nascent formation of lamellipodium, it is truly essential to the subsequent cell's elongation and growth [124125]. The assembly dynamics of myosin II's interaction with integrin engagement plays important roles in regulating the components of cancer cell migration during tissue setting [45].…”
Section: Roles Of Myosins In Tumor Invasion and Metastasis Developmentmentioning
confidence: 99%